Comparative analysis of ducks liver gene expressions infected with virulent or attenuated DHAV-3 reveals divergent host responses to viruses of different virulence - Fu, Qiuling; Jiao, Wenlong; Wan, Chunhe; Wang, Weiwei; Su, Jingliang; Liu, Xiaolong; Cheng, Longfei; Chen, Hongmei; Liu, Jinhua; Huang, Yu; Fu, Guanghua (Frontiers in Microbiology, 2026)
IntroductionDuck hepatitis A virus type 3 (DHAV-3) causes acute fatal hepatitis in ducklings.MethodsThis study compared host transcriptomic responses in duck livers following infection with virulent (HB) or attenuated (HB80) strains.ResultsRNA sequencing (RNA-Seq) revealed that the virulent HB strain induced 2,355 differentially expressed genes (DEGs) at 2 days post-infection (dpi), compared to only 322 DEGs triggered by the attenuated HB80 strain. Functional analysis showed that the HB strain robustly activated immune pathways, particularly Toll-like receptor (TLR) and RIG-I-like receptor (RLR) signaling, leading to a potent type I interferon (IFN-I) response and marked chemokine upregulation. In contrast, the HB80 strain elicited a markedly milder immune reaction. Among the DEGs, 77 immune-related genes were identified, with significant enrichment in the IFN-I signaling pathway, suggesting their critical role in initiating an interferon storm and subsequent chemokine upregulation. Selected key genes (IFN-α2, RSAD2, RIG-I, MDA5, TBK1, TLR7) were validated by RT-qPCR and ELISA for targeted protein confirmation.DiscussionOur study findings suggest that paternal care is associated with medical or co-medical professional choices. Further prospective studies are required to determine causal relationships and investigate other factors related to such choices, given the non-association of all other variables in the study.